GaN HEMT gate-driver for achieving high power converter integration levels - Wu, H; Garcia, J.; Castellazzi, A. (2018)
This work proposes a solution for implementing an isolated gate driver for GaN HEMTs based on the previous topology for SiC power MOSFETs. The isolation of the gate driver is realised by the single transformer topology with double winding in the secondary side. The Bi-level HF Amplitude Modulation scheme is retained to avoid the core saturation as well as providing simultaneously both the switching signal and the required gate power in the secondary side which ensures the full range duty ratio. The reconstruction of the original PWM signal is optimised using a simple hysteresis comparing scheme, which is the Schmitt Trigger circuit, to avoid sudden turn-on or turn-off. The experiment result shows that the Schmitt Trigger circuit could effectively avoid the sudden turn-on or turn-off but it might have some negative effect on the accuracy of duty circle. Finally, the feasibility of the gate driver is demonstrated with the PGA26E19BA GaN device with optimised final power stage.